Surface downwelling shortwave radiation flux projections for 2021-2050 in Morocco according to CORDEX-Africa regional climate models : Projekcije površinskoga dolaznog kratkovalnog zračenja za razdoblje 2021.-2050. u Maroku prema CORDEX-Afrika regionalnim klimatskim modelima - El Hadri, Youssef (Array, 2021)
The article considers the results of an estimation of the shortwave radiation flux at the surface in Morocco from 2021-2050. Average monthly values of shortwave radiation coming to the underlying surface (Surface Downwelling Shortwave Radiation, RSDS), calculated using 11 regional climate models of the CORDEX-Africa project, were used as input data. The model calculation was performed assuming a greenhouse gas concentration scenario of RCP4.5. The aim of the work is to determine the characteristics of the distribution of shortwave radiation over the territory of Morocco from 2021-2050 and to identify areas with favourable conditions for developing solar energy in the near future. The results of an analysis of annual RSDS values in the vicinity of the solar power station in Ouarzazate in 2021-2050 are also presented.